The Isaac Newton school of driving : physics & your car - Parker, Barry R. (Johns Hopkins University Press, 2003)
For some people, driving is an art, for others, it's a science. At the Isaac Newton School of Driving, though, every car is a laboratory on wheels and every drive an exciting journey into the world of physics. This books is based on Parker's classroom discussions at Idaho State U. where he discovered a winning teaching formula combining physics with automotive examples. This book describes nearly every aspect of physics as they related to cars; from basic mechanics including velocity, acceleration, momentum, and torque, to more advanced concepts including heat transfer and efficiency, electricity and magnetism, and aerodynamics.